High-Velocity Suspension Flame Spraying (HVSFS), a new approach for spraying nanoparticles with hypersonic speed - Killinger, A.; Kuhn, M.; Gadow, R.
The fabrication of nanostructured coatings by means of thermal spray techniques is a challenging approach with new applications in mind. However, it requires the processing of very fine-grained powders with a grain size in the nanoscale. As nano- and submicrometer powders cannot be processed using mechanical powder feeders, new concepts have to be developed. Among these, suspension spraying is one of the most promising. High-velocity suspension flame spraying (HVSFS)is a new approach to spray micron, submicron or nanoparticles with hypersonic speed with the aim to form thin and dense coating layers. For this purpose, the powder is dispersed in aqueous or organic solvent and fed axially into the combustion chamber of a modified High-Velocity Oxyfuel (HVOF)spray torch. Several suspension feeder concepts were tested to ensure a constant flow of the suspension and, thus, a stable spray process. Different oxide materials were processed in form of a suspension containing submicrometer- or nanosized powders consisting of alumina, titania and yttrium stabilized zirconia (YSZ). The paper gives an introduction to HVSFS technology and will present first experimental results.
Keywords: HIGH-VELOCITY SUSPENSION FLAME SPRAYING; SUSPENSION FLAME SPRAYING; NANOSTRUCTURED COATINGS